Perancangan Aplikasi Analytical Hieararchy Process Berbasis Web Penentuan Penerimaan Beasiswa SMK Negeri 1 Talangpadang - Rima Mawarni; Meri Parida (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Systemic data processing is a necessity that is immediately implemented in all service lines both government, education and trade. Scholarship data processing at SMK Negeri 1 Talangpadang still uses a manual system in the form of manually storing data in the Ecxel office application. The problem that often arises is the scattered distribution of scholarship receipt files each year. Scholarship selection criteria consist of Academic Achievement, NonAcademic Achievement, Personality, Mileage, Report card grades, Organizational, Parental dependents, Parents' income, and Parental status. The method used in this deccision making system is the Analytical Hierarchy Process method. In the process of developing an application using a structured model by planning it uses a use case diagram. The application system was developed by using the HTML programming language and MySQL Data Base then tested using the localhost system with the Xammp application.